The roles of endothelial nitric oxide synthase (eNOS) and myeloperoxidase (MPO) genes in microtia - Büyükgüral, Berker; Pehlivan, Sacide; Feyda Nursal, Ayfle; Bekerecioğlu, Mehmet (ENT Updates, 2016)
Objective: The aim of this study was to determine the relationship between polymorphisms of endothelial nitric oxide synthase (eNOS) and myeloperoxidase (MPO) genes and development of microtia. Methods: Nineteen (11 males, 8 females) unrelated cases with microtia and 40 healthy controls were enrolled in the present study. The study focused on three functional variants; a variant in exon 7 (G894T) and a variable number of 27 bp tandem repeats in intron 4 (VNTR) of eNOS gene and a variant in the promoter region (G463A) of MPO gene. We genotyped these variants using the polymerase chain reaction (PCR) and/or PCR-restriction fragment length polymorphism (RFLP) method. The distribution of allele and genotype in eNOS and MPO genes were compared between cases with microtia and healthy controls using chi-square test. Results: With regard to the eNOS (G894T) variant, there was a significant difference in genotype distribution between cases with microtia and healthy controls (OR: 1.267, 95% CI: 1.004–1.598; p=0.009). Our study demonstrated that cases with eNOS (G894T) TT genotype had increased risk of microtia. The allele frequencies of eNOS (VNTR) variant showed statistically significant difference between cases with microtia and healthy controls (OR: 2.947, 95% CI: 1.188–7.311; p=0.028). eNOS (VNTR) B allele was higher in the cases. However, there was no significant difference for MPO (G463A) variant according to genotype distribution and allele frequency between cases with microtia and healthy controls. Conclusion: To the best of our knowledge, this is the first analysis of the eNOS (G894T and VNTR) and MPO (G463A) variants in cases with microtia. Our data demonstrate that eNOS gene variants might play crucial role on the etiopathogenesis of microtia in Turkish population. The findings of the current study highlight the necessity for prospective longitudinal studies in elucidating the relative contributions of various factors in diseases with a multifactorial etiology where there is interplay among genetic susceptibility and exogenous factors.